Does Acupressure Hit the Mark? A Three-Arm Randomized Placebo-Controlled Trial of Acupressure for Pain and Anxiety Relief in Athletes With Acute Musculoskeletal Sports Injuries. Issue 4 (July 2017) - Mącznik, Aleksandra K.; Schneiders, Anthony G.; Athens, Josie; Sullivan, S. John
Abstract : Objectives: Injuries are a common consequence of sports and recreational activity. The optimal management of symptoms is a crucial element of sports injury management. Acupressure has previously been shown to effectively decrease symptoms of musculoskeletal injury, thus may be considered a potentially useful intervention in the management of sport-related injuries. Therefore, this study was conducted to examine the effectiveness of acupressure in decreasing pain and anxiety in acutely injured athletes. Design: A prospective 3-arm randomized placebo-controlled trial. Setting: A sports injury clinic, Dunedin, New Zealand. Patients: Seventy-nine athletes who sustained a sport-related musculoskeletal injury on the day. Intervention: Three minutes of either acupressure, sham acupressure, or no acupressure. Main Outcome Measures: The primary outcomes of pain and anxiety intensity were measured before and immediately after the intervention on a 100-mm visual analog scale (VAS). Pain and anxiety relief, satisfaction with treatment, willingness to repeat a similar treatment, and belief in the effect of acupressure were secondary outcomes measured on Likert scales after the intervention. Results: The acupressure group reported 11 mm less pain (95% CI: 5-17) on average than the sham acupressure group, and 9 mm less (95% CI: 3-16) than the control group as a result of the intervention ( P < 0.05). There was no difference between groups in: anxiety levels, or in any of the secondary outcome measures. Conclusions: Three minutes of acupressure was effective in decreasing pain intensity in athletes who sustained an acute musculoskeletal sports injury when measured on the VAS, but did not change anxiety levels.